Evaluating the Impact of Smoking and Hyperlipidemia in Patients with Atherosclerotic Cardiovascular Disease : Smoking and Hyperlipidemia in Atherosclerosis - Raza, Hassan; Idrees, Beya; Khan, Hasaan Ullah; Bakhtiar, Kainat; Ahmed, .; Ahmad, Sobaan; Shuja, Arslan (Pakistan Journal of Health Sciences, 2024)
Hyperlipidemia and Smoking are risk factors of atherosclerotic cardiovascular disease in Pakistani community. Objectives: To determine whether smoking and hyperlipidemia were associated with atherosclerotic cardiovascular disease. Methods: A comparative, cross-sectional study was conducted upon a sample of 200 male and female participants with different cardiac complications were selected and divided them into different groups like Group A and Group B. The individuals with medical complications such as severe chest pain, unexpected numbness or weakness in arms or legs and loss of vision were placed in Group A. While in Group-B 70 male and 30 female individuals with mild chest pain were include. BMI, Cholesterol, Triglyceride, LDL and HDL levels and other demographics such as age, smoking habits were measured respectively. Results: In Group A (severe disease group) there were 75 males and 25 females while in Group B (mild disease group) 70 male and 30 female individuals were listed. The mean age in Group A (59.09 ± 0.01) and Group B (59.09 ± 0.01). The results showed significant difference in Group A and B mean cholesterol (279.9 ± 0.04 vs. 239.09 ± 0.04), Triglycerides (187.02 ± 0.01 vs. 127.02 ± 0.01), LDL (153.01 ± 0.02 vs. 123.01 ± 0.02), HDL (49.04 ± 0.01 vs. 40.01 ± 0.01) and (p value<0.05). Conclusions: It was concluded that hyperlipidemia and smoking were significant (p≤0.05) risk factors for atherosclerotic cardiovascular disease, as seen by increasing levels of cholesterol, Triglycerides and LDL in cardiovascular patients.